Comparative review of allowances types for dividing a benefit with indivisible items - V. V. Egorov (Вестник университета)
The article studies the issues related to the problem of sharing by two beneﬁciaries of a resource with a set of indivisible components. Several types of sharing that consider “envy” and realize it, including through compensatory payments to the beneﬁciary who does not get the corresponding indivisible component of the resource, have been noted. The difference between the values of possible bonuses at different types of sharing, which are received in addition to the values declared by the beneﬁciaries, and indivisible components when they are evaluated, has been determined. It has been found in which case it is more favorable for the beneﬁciary if “envy” is not considered, and vice versa. The method of setting the degree of preference of considering “envy” in the course of distribution of resource components has been proposed, assuming a preliminary agreement of beneﬁciaries on the use of this method. The result of using it has been analyzed, based on which recommendations to the beneﬁciaries are formulated, implying additional awareness not covered in the present study. In order to circumvent the issue of uninformedness, indications of one option of its solution have been presented, which can be considered also as possible future directions of research of stochastic nature.